2010
DOI: 10.1007/s11277-010-9953-3
|View full text |Cite
|
Sign up to set email alerts
|

A Living Laboratory Exploring Mobile Support for Everyday Life with Diabetes

Abstract: The paper presents the set up of a Living Laboratory in a city of North Denmark exploring mobile support for everyday life with diabetes. Background and definitions of the living lab method is presented together with descriptions of the technical setup, applications and explorations. The living lab method was practiced over two iterations-one in 2008 and one in 2009. 17 diabetes families, 9 service providers, researchers and ICT-consultants has participated in the activities. The results present how the living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Furthermore, technical issues and a small user base generated dropout among the participants. This finding is in line with Kanstrup, Bjerge, and Kristensen (2010), who argue that users dropout when the technology is unstable. Finally, for the third field trial, time restrictions caused non-participation in the assignments, as was also found by Simons, Hampe, and Guldemond (2013).…”
Section: Factors Affecting the Attrition Of Test Users During Living supporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, technical issues and a small user base generated dropout among the participants. This finding is in line with Kanstrup, Bjerge, and Kristensen (2010), who argue that users dropout when the technology is unstable. Finally, for the third field trial, time restrictions caused non-participation in the assignments, as was also found by Simons, Hampe, and Guldemond (2013).…”
Section: Factors Affecting the Attrition Of Test Users During Living supporting
confidence: 90%
“…Kanstrup, Bjerge, and Kristensen (2010) argue that the stability of the ICT infrastructure and some kind of user support are factors that decrease the rate of attrition, but do not make a distinction between dropout and non-usage attrition.…”
Section: Factors Affecting the Attrition Of Test Users During Living mentioning
confidence: 99%
“…Like using design probes with children [40], using cognitive probes with people with T1D and T2D [24], and conducting participatory design and running a living lab with families [19,20], user-driven design might provide another way forward for self-management tools. This could involve using rapid prototyping and open source hardware and software in creating bespoke mobile medical technology.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, 9 service providers (restaurants, bakeries, super market, tourist office, butcher"s shops) from the city of Skagen in North Denmark participated in establishing the living laboratory for digital health services. For elaborations see [2].…”
Section: Methodsmentioning
confidence: 99%